Research on the Flow Field Characteristics of the Industrial Elliptical Cyclone Separator - Yongli Zhang; Kangshuo Li; Kaixuan Zhang; Guangfei Zhu; Zhanpeng Sun; Jianfang Shi (Separations)
A new type of elliptical cyclone separator has been proposed recently, but the flow field characteristics within the industrial device still need to be further investigated. In this paper, the characteristics of the flow field and particle motion inside the circular cyclone and the elliptical cyclone (with a long-to-short axis ratio of 1.2), with the equivalent hydraulic diameter of 300 mm, are comparatively analyzed using CFD methods. The results show that there is a significant change in the flow field distribution of the elliptical cyclone compared to the conventional circular cyclone. The static pressure gradient of the elliptical cyclone is anisotropic in the radial direction. The overall tangential velocity value is reduced, which reduces friction loss and makes the pressure drop of the elliptical cyclone significantly lower. More importantly, an acceleration/deceleration phenomenon of the airflow velocity occurs in the elliptical separator along the horizontal circumference, that is, the flow field is transformed into a circumferential fluctuating cyclonic field. This phenomenon induces an additional inertial separation effect that compensates for the unfavorable effects caused by the reduced centrifugal strength. Due to the coupling of centrifugal force and additional inertia effect, the residence time of small particles with a diameter of 1 micron in the elliptical cyclone is shorter, which helps to reduce the backmixing of particles and improves the separation efficiency of the elliptical cyclone. This study reveals the unique flow field characteristics of industrial elliptical cyclones, which is helpful to further understand the particle separation mechanism in the circumferential wave swirl field.